Jurnal TAHUN YUBILEUM 2025 SEBAGAI LANDASAN KATEKIS DALAM MENDORONG PARTISIPASI UMAT DALAM PELAYANAN HIDUP MENGGEREJA DI PAROKI SANTO PAULUS SENDANGGUWO SEMARANG: Tema Pastoral - Vinsensius Viktor Armando; Yustinus Joko Wahyu Yuniarto; Timotius Tote Jelahu (Jurnal Pelayanan Pastoral, 2026)
This research aims to examine the meaning of the Jubilee Year 2025 as a pastoral foundation for catechists in encouraging the participation of the faithful in the life of the Church, particularly in the field of liturgy, in Saint Paul Parish Sendangguwo, Semarang. The Jubilee Year 2025, with the theme “Pilgrims of Hope,” is understood by the Church as a moment of grace for the renewal of faith, conversion, and the strengthening of the faithful’s involvement in ecclesial life. Pastoral realities show that the participation of the faithful in liturgical ministry is still relatively low, as indicated by passive attitudes, feelings of unworthiness, and limited understanding of the baptismal calling. This research uses a descriptive qualitative approach with data collection techniques consisting of document study, observation, in-depth interviews, and open-ended questionnaires. The results show that catechists interpret the Jubilee Year 2025 as a strategic pastoral opportunity to awaken the faith awareness of the faithful through catechesis, socialization, and the witness of life. The role of catechists as pastoral agents and examples of faith has a significant influence in increasing the active involvement of the faithful. This study contributes to strengthening pastoral catechetical ministry in the local parish, emphasizing that the authentic appreciation of moments of faith by catechists becomes a key factor in transforming the participation of the faithful in the life of the Church.